Strategic Integration: Fostering Sustainability in Low-Income Country through Poverty Alleviation, Carbon Efficiency, Energy and Economic Resilience - Al-Dhubaibi, Ahmed Abdullah Saad; Khan, Aarif Mohammad; Sharaf-Addin, Hussein H.; Solichin, Mochammad (International Journal of Energy Economics and Policy, 2024)
This study emphasizes the critical importance of strategic integration for sustainable development goals (specifically Goals 1 and 2) in low-income countries (LICs). The research uses econometric models to focus on poverty reduction, economic resilience, energy use, and carbon emissions in Indonesia from 1996 to 2022. The study reveals a long-run co-integration among the estimated parameters, with a significant speed of adjustment at a 1.04% level. ECM models highlight a positive relationship between energy use, poverty, and carbon emissions while indicating a negative association between economic growth and carbon emissions. Robustness checks support these findings, including Fully Modified Ordinary Least Squares (FMOLS) and Canonical Co-Integrating Regression (CCR). Granger causality analysis reveals a unidirectional causality from energy use to carbon emissions and economic growth, along with one-way causation from carbon emissions to economic growth and poverty. Diagnostic tests affirm the model’s reliability. The study’s outcomes contribute valuable insights to the discourse on strategic integration, offering policymakers and stakeholders guidance in formulating sustainable development strategies tailored to the unique challenges encountered by low-income countries.